(3GdYbO GdefXe ddMcGe ajeG jLQi Hjfge ef GdYbhO hGdCMcGes - (3CHh GdbGSe Sdehf Hf Ydj Hf Sdehf GdcfGfj,J (B767 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3bGd GdTjN Gdabjg CHh GdbGSe Sdehf Hf Ydi Hf Sdehf GdcfGfi GdMeO ddg Pi GdeLO hGdcQe GdPi Yde HGdbde Yde GdEfSGf eGde jYde hYdeJ eG LGA ai bhdg Ydjg GdSdGe GdbVGg KdGKI bGVjGf ai GdfGQ hbGV ai GdLfI ef GdhYO hGdhYjO s
(3BNQgG (B:s
(3aUd hCeG GdMjhGf ZjQ GdQbjb ajcJH ajg YbQ ETJQi adGf Hf adGf jYO GdJZdjH hGdQV hGdYde HCf ef YjhHg s
(3HgG fXGe GdJYbjHIs
(3fSNI YdjgG eWGdYI hJUhjHGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B114 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B643s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B111s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs